2021
DOI: 10.31413/nativa.v9i5.12777
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Mixing Formulations for Citrus Nursery Management

Abstract: The length of citrus seedling development is determined by several factors, including the physical and chemical qualities of the substrate, which affect rootstock growth and, as a result, the quality of field seedlings. The purpose of this study was to see how the ‘Swingle’ citrumelo rootstock developed with different substrate formulations. The experiment was carried out in a seedling nursery from seeding to grafting, and six treatments were carried out, as follows: 60% peat moss, 30% fine grade horticultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…The growth dynamics of the tested rootstocks were similar to those of the 'Cravo' rootstock when grown in a pine bark-based substrate (de Almeida et al, 2012). However, they were not similar to the Swingle Citrumelo, which exhibited the most growth during months four and five after transplanting (Sauer-Liberato et al, 2021).…”
Section: Cation Exchange Capacity (Cec)mentioning
confidence: 75%
See 1 more Smart Citation
“…The growth dynamics of the tested rootstocks were similar to those of the 'Cravo' rootstock when grown in a pine bark-based substrate (de Almeida et al, 2012). However, they were not similar to the Swingle Citrumelo, which exhibited the most growth during months four and five after transplanting (Sauer-Liberato et al, 2021).…”
Section: Cation Exchange Capacity (Cec)mentioning
confidence: 75%
“…Sour Orange had the least height and stem diameter, regardless of the substrate. Sauer-Liberato et al (2021) found that Swingle Citrumelo (Citrus paradisi Macf. × Poncirus trifoliata L.) had a plant height of 106.8 cm and a stem diameter of 8 mm after five and a half months of being transplanted into 4 L polyethylene bags.…”
Section: Cation Exchange Capacity (Cec)mentioning
confidence: 99%
“…Dessa forma, o crescente aumento na procura por mudas de espécies nativas tem ressaltado a necessidade de desenvolver protocolos que aprimorem a produção de mudas de alta qualidade, capazes de atender às exigências em campo para futuras plantações (FARIA et al, 2017). Assim, para obter mudas de qualidade é essencial considerar a formulação dos substratos (LIBERATO et al, 2021;DIAS et al, 2022). O uso de resíduos orgânicos na produção de mudas florestais é viável devido aos teores de nutrientes presentes nesses resíduos e à solução para problemas de destinação enfrentados pelas empresas.…”
Section: Introductionunclassified